Bentall Procedure for an Adult Patient with Supravalvular Aortic Stenosis and Coronary Aneurysms. Issue 4 (24th July 2013) - Alzahrani, Haitham; Al‐Shamiri, Mostafa; AlBackr, Hanan; Bakir, Bakir M.; Alsatli, Raed A.; Albacker, Turki B.
Abstract We describe the surgical management of a 35‐year‐old male with multiple coronary aneurysms and a diffuse form of supravalvular aortic stenosis who presented with acute myocardial infarction and left ventricular dysfunction. The patient underwent a Bentall procedure with left internal mammary artery to left anterior descending artery bypass grafting with the use of cardiopulmonary bypass utilizing the right axillary artery for arterial cannulation. doi: 10.1111/jocs.12119 (J Card Surg 2013;28:394–396)